Elephants, rhinos and the economics of the illegal trade - Michael t'Sas-Rolfes (Pachyderm)
Discusses decisions made at the recent CITES meeting, the Tenth of the Parties of the Convention, associated with the international ivory and rhino horn trade. Results give some insight into the realization that a blanket ban was not sustainable in the face of highly different population and ecological situations in various ranges states. Suggests the provisions for the sale of ivory stocks from Botswana, Namibia and Zimbabwe opens the way to alternative views of trade and management in these wildlife products, and for conservation of elephants and rhinos. The paper reviews the issues associated with the stockpiling of ivory, the maintenance of elephant populations and the economics of the illegal trade as well as noting aspects of population control programmes.